Решить уравнение: a) (4x+3)-(10x+11)=7+(13-4x) b) (3-2x)+(4-3x)+(5-5x)=12+7x
Решить уравнение: a) (4x+3)-(10x+11)=7+(13-4x) b) (3-2x)+(4-3x)+(5-5x)=12+7x
Ответ(ы) на вопрос:
Гость
(4х+3)-(10х+11)=7+(13-4х) 4х+3-10х-11=7+13-4х 4х-10х+4х=7+13-3+11 -10х=28 х=-2,8 (3-2х)+(4-3х)+(5-5х)=12+7х 3-2х+4-3х+5-5х=12+7х -2х-3х-5х-7х=12-3-4-5 -17х=0 х=0
Гость
A) 4X=3-10X-11=7+13-4X 4X-10X+4X=-3+11+7+13 -10X=28 X=28:(-10) X=-2,8 Б)3-2x+4-3x+5-5x=12+7x -2x-3x-5x-7x=-3-4-5+12 -17x=-12+12 -17x=0 x=-17:0 x=0
Не нашли ответ?
Похожие вопросы